Study of histopathologic spectrum and microbiologic correlation of sinonasal fungal rhinosinusitis - Mukherjee, Dr Tanushri; Dutta, Dr Rajat; Roy, Dr Ravi; Singh, Dr Nalin (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Fungal Rhinosinusitis is common in sinonasal tract and it can be non-invasive and invasive. Non-invasive when there is either a fungus ball or an allergic fungal rhinosinusitis. Invasive forms present clinically as acute, chronic and chronic granulomatous rhinosinusitis. 100 patients with fungal sinusitis and rhinitis were studied in this study, 88% were non-invasive (46% had allergic fungal rhinosinusitis, 40% Fungus ball , and 2% combined allergic fungal rhinosinusitis, 12% were invasive. Histopathology and fungal isolates confirmed aspergillus sp in 54% of cases, Candida sp in 34% cases however 10% isolates were Penicillium and fusarium and Mucor was found in two percent of cases of invasive mucormycosis.